2016
DOI: 10.1017/s0024282916000323
|View full text |Cite
|
Sign up to set email alerts
|

A revision of theLeptogium saturninumgroup in North America

Abstract: A revision of the North American members of the Leptogium saturninum group (i.e. species with long lower-surface hairs, isidia, and usually smooth upper surface) is presented based on molecular phylogenetic analyses of mtSSU and nrITS sequence data, together with an extensive morphological study. Three species supported by both molecular and morphological characteristics are recognized: L. acadiense sp. nov. (distinguished by granular saturninum-type isidia, medulla composed of irregularly arranged or perpendi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 48 publications
2
14
0
Order By: Relevance
“…Stone 2016); Rosentreter 19268; near mouth of creek at north end of James Lagoon, on Salix bark, Rosentreter 19101; near Park entrance on Exit Glacier Road, floodplain of Resurrection River, on Populus balsamifera, Schultz 16702b; on Alnus bark, Rosentreter 18994; west of Resurrection River and north of Exit Glacier Road, on Populus bark, Rosentreter 19306; on Alnus bark, Rosentreter 19305. As shown byStone et al (2016) and confirmed by us, L. saturninum is polyphyletic, even after four new species were segregated, leaving two main clades of L. saturninum. The specimen we sequenced (Schultz 16702b) falls in the clade with the Scottish epitype(Stone et al 2016, p. 415) and is presumed to be L. saturninum s.str.…”
supporting
confidence: 61%
“…Stone 2016); Rosentreter 19268; near mouth of creek at north end of James Lagoon, on Salix bark, Rosentreter 19101; near Park entrance on Exit Glacier Road, floodplain of Resurrection River, on Populus balsamifera, Schultz 16702b; on Alnus bark, Rosentreter 18994; west of Resurrection River and north of Exit Glacier Road, on Populus bark, Rosentreter 19306; on Alnus bark, Rosentreter 19305. As shown byStone et al (2016) and confirmed by us, L. saturninum is polyphyletic, even after four new species were segregated, leaving two main clades of L. saturninum. The specimen we sequenced (Schultz 16702b) falls in the clade with the Scottish epitype(Stone et al 2016, p. 415) and is presumed to be L. saturninum s.str.…”
supporting
confidence: 61%
“…The development of isidium was considered an important taxonomical characteristic in Leptogium saturninum group (Stone et al 2016). We found different isidia in Rio Grande do Sul specimens, when compared to L. hibernicum type, but further studies are necessary.…”
Section: An Acadmentioning
confidence: 70%
“…— Corticolous on Alnus (5×), Populus balsamifera (1×) and Salix (2×), typically at the back of beach meadows, 0–15 m, also saxicolous once at 937 m. EA: 872, S36601, S36615; nr 438, S39308 (fertile); 440, S39229; 441, F10205; EX: 409, S38895; GUS: 857, F9637, S36139, S36142 (fertile); WA: 391, S38612. We sequenced several loci from a rare, richly fertile specimen (isolate T1731 from S39308) but it does not appear close to any of the species sequenced by Stone et al (2016). The ITS sequence we obtained differs in at least 38 positions from the next nearest published sequence from this group (GenBank Accession MK778616, from Siberia). *# Lichenochora lepidiotae (Anzi) Etayo & Nav.-Ros.…”
Section: Catalogue Of All Named Taxa Foundmentioning
confidence: 88%